BUILDING THE COMMUNICATIVE CULTURE OF MP’S TEAMS AND THE COMMUNITIES - Neprytskyi, Oleksandr; Neprytska, Tetyana; Kyyenko-Romaniuk, Larysa; Melnychuk, Tetyana; Zayachkovskyi, Volodymyr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article studies the issue of establishment of efficient and sustainable communication between a community and an MP and his/her team. Based on the results of focus group discussions, the authors determine and describe the main problems and gaps that exist in parliamentary education of the general public as well as MPs and their teams and outlines the competences and tools necessary for making this communication efficient and mutually beneficial. The aim of the research is to determine the content and methods of the communicative component of parliamentary education for communities and MP’s teams. The methods used include focus group research (to collect the date regarding the mood, views and attitudes of the public and the MPs and their teams); information analysis and synthesis (to structure the collected data and draw conclusions from it). The study showed a considerable lack on behalf of the public to participate in building the communication, a high level of incompetence on both sides that derives from the lack of systemic parliamentary education and the need to systemically use the same communication channels in order to ensure effective and sustainable interaction of the public with the elected officials.